6(3+x)=5(x-6)

Simple and best practice solution for 6(3+x)=5(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3+x)=5(x-6) equation:


Simplifying
6(3 + x) = 5(x + -6)
(3 * 6 + x * 6) = 5(x + -6)
(18 + 6x) = 5(x + -6)

Reorder the terms:
18 + 6x = 5(-6 + x)
18 + 6x = (-6 * 5 + x * 5)
18 + 6x = (-30 + 5x)

Solving
18 + 6x = -30 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
18 + 6x + -5x = -30 + 5x + -5x

Combine like terms: 6x + -5x = 1x
18 + 1x = -30 + 5x + -5x

Combine like terms: 5x + -5x = 0
18 + 1x = -30 + 0
18 + 1x = -30

Add '-18' to each side of the equation.
18 + -18 + 1x = -30 + -18

Combine like terms: 18 + -18 = 0
0 + 1x = -30 + -18
1x = -30 + -18

Combine like terms: -30 + -18 = -48
1x = -48

Divide each side by '1'.
x = -48

Simplifying
x = -48

See similar equations:

| 4a=2(a+2)-12 | | y-3=2(-1+1) | | 7(10)+7(10)+12(10)=360 | | 3+x+5-2x=78 | | 4x(2x-7)=112 | | 3x+5[2-4(x-2)]=x-4 | | 24v^4+78v^3b-21v^2b^2=0 | | Y=2ax-9x-9b | | 3+x-5+2x=78 | | -3[x+(-8)]=56 | | 4x+17=2x | | 126=10+4p | | 7x+42=-18-3x | | F(x)=11x-1 | | [x-2]=-2 | | 195=12+x | | 2y=103-x | | 5(x+5)+8(-x+8)=77 | | 3x-15+6x+1=45 | | -4(x-1)=9x+9 | | .5(10+12n)=.3333(15n+15) | | -4(x+6)=-4(x+2)-x | | 8(5c-1)-18=38c+8 | | -1=t+(-18) | | 8c^2-20c-12=0 | | 3.5(9)+3.5(9)+12(9)=180 | | 9x-6x-2=1 | | y=x^3-13x | | 7x+1=-2x+37 | | 6t+3(5t-4)=12(2t-2w) | | -16x-3=x-67 | | n^2+7.58333333333n=0 |

Equations solver categories